Case report: Aborted sudden cardiac death as a first presentation of severe mitral annulus disjunction—a case series and review of the literature - Apostolou, Fay; Ioannides, Marios; Mitsis, Andreas; Koutsofti, Constantina; Deltas, Constantinos; Avraamides, Panayiotis (Frontiers in Cardiovascular Medicine, 2023)
Mitral annular disjunction (MAD) is a structural, congenital abnormality in mitral annulus fibrosus manifested as a displacement of the left atrial wall-mitral valve junction, and the basal inferolateral left ventricular wall. It is commonly co-existent with myxomatous mitral valve disease, mitral valve prolapse (MVP). The first diagnostic modality aiding the diagnosis is transthoracic echocardiography (TTE), although in some cases a further cardiac imaging modality might be suggested. MAD carries a strong association with malignant ventricular arrhythmogenesis and a profound predisposition for sudden cardiac death (SCD). In this context a thorough investigation of this morphological and functional abnormality is vital in estimating the risk assessment and stratification for an optimal management and elimination of the patient’s risk for SCD. Based on the current scientific data and literature, we will discuss the diagnosis, clinical implications, risk stratification and therapeutic management of MAD. A minimal case series will reveal the most significant, malignant consequence of this anatomical variation in its full context of presentation.